Solvent‐Mediated Shell Dimension Reconstruction of Core@Shell PdAu@Pd Nanocrystals for Robust C1 and C2 Alcohol Electrocatalysis. Issue 32 (2nd July 2021) - Gao, Fei; Zhang, Yangping; You, Huaming; Li, Zhuolin; Zou, Bin; Du, Yukou
Abstract: The core@shell structure dimension of the Pd‐based nanocrystals deeply impacts their catalytic properties for C1 and C2 alcohol oxidation reactions. However, the precise simultaneous control on the synthesis of core@shell nanocrystals with different shell dimensions is difficult, and most synthesis on Pd‐based core@shell nanocatalysts involves the surfactants participation by multiple steps, thus leads to limited catalytic properties. Herein, for the first time, a facile one‐step surfactant‐free strategy is developed for shell dimension reconstruction of PdAu@Pd core@shell nanocrystals by altering volume ratios of mixed solvents. The Pd‐based sunflower‐like (SL) and coral grass‐like (CGL) nanocrystals are obtained with different 2D hexagonal nanosheet assembles and 3D network shells, respectively. Benefitting from the clean surface shell of 2D ultrathin nanosheets structure, high atom utilization efficiency, and robust electronic effect. The PdAu@Pd SL achieves the ascendant methanol/ethanol/ethylene glycol oxidation reaction (MOR/EOR/EGOR) activities, much higher than Pd/C catalysts, as well as the improved antipoisoning ability. Notably, this one‐step construction shell dimension of PdAu@Pd core@shell catalysts not only provide a significant reference for the improvement of surfactant‐free synthetic routes, but also shed light on the advanced engineering on shell dimensions in core@shell nanostructures for electrocatalysis and so forth. Abstract : A facile one‐step and surfactant‐free method is adopted to prepare core@shell PdAu@Pd nanocrystals. The PdAu@Pd with different shell dimensions are precisely reconstructed by altering the ratios of cosolvents. PdAu@Pd SL with 2D hexagonal shell exhibits fast mass transport, high atomic utilization, and optimal geometric effects, which deliver much higher than Pd/C catalysts toward methanol/ethanol/ethylene glycol oxidation reaction (MOR/EOR/EGOR).